Implementation of Problem Based Learning Model to Improve Student Learning Outcomes in Islamic Education Learning at SD Negeri 341 Batahan - Musridannur (MANDAILING GLOBAL EDUKASIA, 2025)
This study aimed to investigate the implementation of the Problem-Based Learning (PBL) model to improve student learning outcomes in Islamic Education at SD Negeri 341 Batahan. The research focused on examining how PBL could enhance student engagement, critical thinking, collaboration, and the application of Islamic values. The study utilized a mixed-methods approach, collecting data through pre- and post-tests, classroom observations, student feedback, and teacher reflections. The findings indicated a significant improvement in students' learning outcomes, with post-test scores showing higher performance compared to pre-test results. Additionally, students demonstrated increased engagement, motivation, and participation in the learning process. The PBL model also fostered enhanced critical thinking, communication, and collaboration skills. Furthermore, students were able to apply Islamic values more effectively to real-world issues. Despite challenges such as managing group dynamics and ensuring equal participation, the overall results suggest that PBL is a highly effective teaching strategy in Islamic Education. The study concludes that PBL can create a more interactive, student-centered learning environment that promotes both academic success and the development of essential life skills.